Assessing the Perception and Contribution of Mangrove Ecosystem Services to the Well-Being of Coastal Communities of Chwaka and Menai Bays, Zanzibar - Mohamed Khalfan Mohamed; Elhadi Adam; Colbert M. Jackson (Resources, 2024)
The mangroves in Zanzibar are crucial to the survival of the local population, as they provide essential ecosystem goods and services. However, the actual value of mangrove products is not easily recognized. As a result, it is chiefly concluded that mangrove forests should be converted to uses that generate directly marketable products. This research sought to assess the perception and value of mangrove ecosystem services to the local communities around the Chwaka and Menai Bays. Key informant interviews, focus group discussions, and household surveys were used to collect data. The chi-squared test and one-way ANOVA were used to compare the awareness and perception of mangrove ecosystem services, respectively. The results show that provisioning services were the mangrove ecosystem services most identified by the household surveys, i.e., c. 84%. Supporting, regulating, and cultural services were rated in that order by 46.2%, 45.4%, and 21.0% of the respondents, respectively. This study found that there were statistically significant differences between Chwaka, Charawe, Ukongoroni, Unguja Ukuu, and Uzi wards in terms of households’ awareness of regulating services (χ2 = 6.061, p = 0.014) and supporting services (χ2 = 6.006, p = 0.014). There were no significant differences in the identification of provisioning (χ2 = 1.510, p = 0.919) and cultural (χ2 = 1.601, p = 0.901) services. Occupations did not determine the reliance on mangrove ecosystem services (χ2 = 8.015; p = 0.1554). The approach used in this study can provide policymakers and land planners with a framework for the sustainable management of the ecosystem services provided by mangroves.